Politik Hukum Pemerintah Indonesia Tentang Perwakafan: Tarik Ulur Kepentingan - Hidayat, Rahmat; Tiswarni, Tiswarni (Prodi Tata Negara (Siyasah) IAIN Langsa, 2024)
This research explains how the government legal politics in the field of waqf with the tug-of-war of various interests that influence this, both the interests of the government, society and the waqf law itself. To achieve this goal the author uses library research, where the data sources were obtained from books and articles that were offended by the topics discussed. Data was sorted out and analyzed using content analysis. This study found that the government legal politics regarding waqf can be seen from the condition of the government's relationship with Muslims. When the government's relationship with Muslims is tenuous, then the rule of Islamic law